Penerapan media kartu huruf untuk meningkatkan kemampuan membaca siswa kelas I SD Negeri 1 Sumilir Purbalingga tahun pelajaran 2020/2021 - Dewi Bayu Utami (Perkumpulan Kualitama Edukatika Indonesia, 2020)
The research aims to improve the reading skills of grade I students by implementing letter cards. The research subjects were Grade I students of SD Negeri I Sumilir with a total of 12 students. Classroom action research was conducted in 3 cycles. Each cycle consists of 1 lesson hour. The procedure for implementing each cycle includes planning, implementing actions, observing, and reflecting. Data collection was obtained from teacher activity observation sheets, student activity observation sheets, and students' understanding scores. For data on students' understanding scores obtained from the evaluation test. Based on the results of classroom action research, the results of observations of teacher activity in the first cycle obtained a score of 3.13 and the second cycle obtained a score of 3.25. The results of observations of student activity in the first cycle obtained a percentage of 70.8% and the second cycle obtained a percentage of 78.25%. The results of the students' understanding value in the first cycle obtained an average of 69.16 completeness 50% and the second cycle became 73.33 completeness 75%. Thus, the application of letter card media can improve the reading skills of grade I students of SD Negeri 1 Sumilir.